Legal Protection Against The Consumer For Unlawful Actions Conducted By Business Personnel - Asa Prayoga Jiwangga; Tutiek Retnowati (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2021)
This study aims to determine and analyze the form of legal protection and the consequences of an illegal act committed by a business actor in violating an agreement and done intentionally. The research method in this study uses a normative research method and uses the statute approach method (statutory approach) and the conceptual approach (concept approach). The result of this study is that legal protection is one of the legal certainties that is in the spotlight of the Indonesian government so that Indonesian citizens can carry out normal activities in the community without fear of an act that is detrimental to them. Legal protection for consumers is a reference for the government in reducing arbitrary attitudes by businesses and consumers. As evidence of the government's efforts to protect consumer rights, Law Number 8 of 1999 concerning Consumer Protection or commonly abbreviated as the Consumer Protection Act was born. One of the actions that often occur as a result of arbitrary attitudes committed by business actors is an act against the law as stipulated in article 1365 of the Civil Code. As a form of legal protection, sanctions or compensation for the consequences of unlawful acts is applied. The application of sanctions or compensation is not formulated in Article 1365 of the Civil Code, but the application of sanctions or compensation is applied through a district court decision.